From Fabrication to Characterization of 3D Organic Microresonators: A Complementary Alliance of Microfluidics and Optics. (8th November 2012) - Pluchon, David; Huby, Nolwenn; Moréac, Alain; Panizza, Pascal; Bêche, Bruno
Abstract : This paper introduces a preview of targeted current research on organic optofluidic materials and devices devoted to 3D photonics microresonators (MRs). First, such an approach takes advantage from a significant know-how on optical simulations of 3D spherical MRs by complementary and coupled ways based on electromagnetism and quantum mechanics principle. Such simulations have allowed to preset the quantization of whispering gallery modes (WGMs) and to define a new formulation of optical caustics in global 3D MRs cavities. Leaning from these simulations, an interdisciplinary approach has been achieved by combining microfluidics techniques and thin layer processes that allowed with flow rates control the realization of 3D droplets MRs of several tens of micrometers in radii. Finally, free-space optical characterizations have been performed on such 3D polymeric MRs by judicious protocols based, respectively, on a modified Raman spectroscopy laser excitation and an adequate direct beam waist optical coupling. Spectral analysis on such 3D MRs of various sizes confirms the excitation of the expected WGMs revealing free spectral range (FSR) and caustics values close to the analytical ones.